Demand Uncertainty and Manual Packaging System Toward Supply Chain Resilience (Universitas Terbuka, 2025)
Supply chain resilience is a challenge for manufacturing companies amidst market demand uncertainty and operational limitations, one of which is the manual packaging system at PT. Songgolangit Persada, a manufacturing industry producing EM4 fishery probiotics. The study was conducted to determine how demand uncertainty, manual packaging systems, and supply chain resilience at PT. Songgolangit Persada. Data were collected by distributing questionnaires filled out by 50 respondents of PT Songgolangit Persada production staff and quantitative methods. Data were analyzed using SmartPLS 3. The analysis stated that demand uncertainty was not significant with supply chain resilience with a p-value of 0.905 (> 0.05). The manual packaging system had a significant negative effect with a p-value of 0.000 (< 0.05). Limitations in operational technology at the packaging stage can be a factor that reduces supply chain resilience. This study provides a theoretical contribution to the supply chain management literature by combining two important operational factors. Practically, these results provide implications that modernizing packaging systems and investing in automation technology are important strategies to improve supply chain efficiency and adaptability. Future research could explore additional variables such as the use of automation technology and risk mitigation strategies within the broader context of supply chain disruptions.